Neutralizations of adults committing different crimes: Variety, prevalence and connection with criminal experience - Tarozienė, V. (Psichologija, 2010)
There is a lack of information about neutralizations used by adult criminals who have committed different crimes. Moreover, very little is known about the mechanism of neutralization establishment and changes of prevalence in groups of people with different criminal experience, and the available data are controversial. According to G.M.Sykes, D.Matza (1957), neutralizations are learned together with the conduct of crime and do not change in prevalence with increasing criminal experience. Other researchers conclude that with accumulation of antisocial experience, the need of neutralization reduces. The aim of this investigation was to identify neutralizations of adult convicts who have committed different crimes and to test the effect of criminal experience on neutralization. There were three goals of the recent study: 1) to identify the prevalence of neutralization in groups of adult convicts who committed property, violence, mixed (robberies) and illegal disposal crimes; 2) to compare the frequency of different neutralizations used by adult convicts who have committed different crimes; 3) to test the effect of criminal experience, as well as of interaction of criminal experience and the type of crime on neutralization. The social information processing model (Crick and Dodge, 1994) complemented with the neutralization process (Sykes and Matza, 1957) was chosen as a theoretical background of the study. We state that neutralizations are the interpretation process in the second step of the social information processing model. Neutralization of adult men who had committed property (theft), violence (murder, aasault), mixed (robbery) and illegal disposal (drugs, alcohol) crimes was investigated. Participants of the research were divided into two groups by the amount of previous convictions. A supra-secondary analysis of data collected during the program “One to one” (Priestley, 2008) was performed. Two investigators coded different types of neutralizations in semi-structured interview protocols about crimes committed by participants (n = 67). Coded information about the frequency of different types of neutralization as well as scores of the violence neutralization scale (Agnew, 1994) (n = 161) were processed in the further statistical analysis.The results of the research showed that the types of neutralization were significantly related to the type of crime committed by adult convicts (p < 0.001). The prevalence of neutralizations varied in groups of men who had committed different crimes. Men who had committed crimes with elements of violence (violent crimes and robberies) mostly used denial of responsibility and denial of victim (above 80% of group participants). Men who had committed crimes without elements of violence (property and illegal disposal crimes) mostly used denial of harm (about 85% of group participants). Groups of convicts who had committed different crimes significantly differed in the rates of two neutralizations: denial of harm (p < 0.01) and denial of victim (p < 0.01). Men who had convicted property crimes used denial of harm and men who had convicted of violent crimes used denial of victim more often than convicts in other groups. Results of this investigation show that convicts can use several different neutralizations at a time. There was an insignificant main effect of the amount of criminal experience on the frequency of neutralization (p > 0.05). Neither there was a significant interaction between the criminal experience and the type of crime on the frequency of neutralization (p > 0.05).
Keywords: neutralization; criminal behavior; criminal experience